Guanylin-like peptides, guanylate cyclase and osmoregulation in the European eel ( Anguilla anguilla ) - Kalujnaia, Svetlana; Wilson, Gillian Dawn; Feilen, Anja Louise; Cramb, Gordon (General and Comparative Endocrinology, 2009)
Three guanylin-like peptides, guanylin, uroguanylin and renoguanylin and two guanylate cyclase type C (GC-C) receptor isoforms were cloned and sequenced from the European eel (Anguilla anguilla). All peptides and both receptors (GC-C1 and GC-C2) were predominantly expressed within the intestine and kidney of both sexually immature yellow, and sexually maturing, migratory silver eels. The derived amino acid sequences for the pre-prohormones and guanylate cyclase isoforms had structural features in common with sequences previously reported for guanylin-like peptides and guanylate cyclases from teleost fish and other species in general. The highest sequence homologies for the prohormones were found within the active, 15-16 amino acid C-terminal peptide domain, whereas the guanylate cyclase receptors exhibited highest homology throughout the transmembrane domain and intracellular region of the protein comprising the kinase homology, oligomerisation/coiled-coil and catalytic domains. In both yellow and silver eels, seawater (SW) acclimation induced sustained increases in the expression of uroguanylin and GC-C1 mRNAs within the intestine but no significant changes were found in the abundance of mRNAs for guanylin, renoguanylin or GC-C2. Likewise there were no significant changes in expression of any of the prohormone or receptor mRNAs within the renal kidney following transfer to SW. The results suggest that uroguanylin and GC-C1 are key components of a cGMP signalling system that may play an important role within intestinal enterocytes for the regulation of salt and water absorption in the SW-acclimated eel. (c) 2008 Elsevier Inc. All rights reserved.